1992
DOI: 10.1093/hmg/1.4.255
|View full text |Cite
|
Sign up to set email alerts
|

Moderate instability of the trinucleotide repeat in spino bulbar muscular atrophy

Abstract: Increased length of a protein-coding CAG repeat within the androgen receptor gene appears to be the only type of mutation responsible for spino-bulbal muscular atrophy (SBMA or Kennedy disease). We have analysed a large 4-generation SBMA family and found that the mutant allele was unstable upon transmission from parent to child, with a documented variation from 46 to 53 repeats and a tendency to increase in size (7 increases and a single decrease in 17 events), which appeared stronger upon transmission from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(34 citation statements)
references
References 0 publications
4
30
0
Order By: Relevance
“…Variations in size of the AR locus DNA repeats have been correlated with certain diseases (Biancalana et al 1992). However, there was no difference in the distribution of allele sizes between mothers of gay men and controls, and a previous analysis on a large number of our samples showed that variations in the AR gene are not a common determinant of male sexual orientation (Macke et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Variations in size of the AR locus DNA repeats have been correlated with certain diseases (Biancalana et al 1992). However, there was no difference in the distribution of allele sizes between mothers of gay men and controls, and a previous analysis on a large number of our samples showed that variations in the AR gene are not a common determinant of male sexual orientation (Macke et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence-or tissue-specific nucleosome positioning in the flanks may affect the priming sites of Okazaki fragments 28 . In this manner, the different chromosomal contexts might explain the variable amounts of instability of similar lengths of CTG/CAG tracts observed at the DM1 locus compared with those observed at the locus associated with spinobulbar muscular atrophy 2,11,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Complete allelic association between the DM1 expansion and several insertion/deletion polymorphisms flanking the repeat 12,13 show that a specific chromosomal background is associated with (CTG) n instability, which suggests that chromosomal context and ciselements may be required for expansion. The variable stability of similar CAG tract lengths at different disease loci provides further support for a role of flanking sequences 2,11,14,15 . Transgenic mouse models of TNR instability also indicate that ciselements that flank the repeat tract may 'drive' repeat instability 16,17 .…”
Section: Introductionmentioning
confidence: 88%
“…PCR amplification of these repeats allows rapid assessment for loss ofheterozygosity and can greatly simplify procedures for mapping tumor suppressor genes (10)(11)(12)(13). More recently they have been used to identify specific mutations in certain inherited disorders including Huntington disease (HD), fragile X syndrome (FX), myotonic dystrophy (MD), spinocerebellar ataxia type I (SCA1), spinobulbar muscular atrophy (SBMA), and hereditary dentatorubral-pallidoluysian atrophy (DRPLA) (14)(15)(16)(17)(18)(19)(20). These inherited disorders appear to arise from the expansion of trinucleotide repeat units within susceptible genes.…”
mentioning
confidence: 99%